Hyko: winter habitat of wild swans at Suibara - Lesser, Rose (Wildfowl, 1973)
The winter home of up to 1,000 Whooper Swans Cygnus cygnus at Hyko, Japan, is described. The swans are artificially fed and given complete protection on a small (18 ha) reservoir on the outskirts of the town. Details are given of the past history of the area, the build-up in swan numbers, and some of their food plants.